The Promoting Effects of Fermented Bile Acid on Growth Performance and Intestinal Health of Litopenaeus vannamei Through the Modulation of Lipid Metabolism and Gut Microbiota - Qing Guo; Haili Ma; Lu Zhao; Wenwen Liu; Houfa Zhao; Zuyue Liu; Cuimin Mu; Xuepeng Wang (Aquaculture Nutrition)
Two types of bile acids (BAs), named fermented bile acids (FBAs) and 170HDa, were produced by a biological approach to assess their effects on growth performance, metabolism, and intestinal health in white shrimp. In this study, five experimental diets were prepared with varying levels of FBAs (0.02% for A1, 0.03% for A2, 0.04% for A3, 0.05% for A4, and 0.06% for A5) and five diets containing different concentrations of 170HDa (0.02% for B1, 0.03% for B2, 0.04% for B3, 0.05% for B4, and 0.06% for B5). Additionally, positive diets (P) with commercial BAs at a level of 0.04%, along with and negative diet (N) without BA supplementation, were included as controls. FBAs and 170HDa were found to improve the growth performance including final weight, weight gain, and specific growth rate and reduce the activities of aspartate aminotransferase and alanine aminotransferase in hemolymph. The alkaline phosphatase (AKP) activity of hemolymph in shrimp treated with FBAs was generally higher than in groups treated with 170HDa and the control groups. However, the acid phosphatase (ACP) activity of hemolymph in shrimp treated with FBAs showed similar levels to those treated with 170HDa and the control groups. The gene expression levels of antilipopolysaccharride factor (ALF) and proPO were significantly lower in most FBAs and 170HDa-treated groups compared to the control groups (p<0.05). Additionally, the gene expression levels of α2M in hepatopancreas were significantly higher in the 170HDa-treated groups compared to those in the FBAs-treated group (p<0.05). The FBAs and 170HDa significantly enhanced the intestinal health by boosting the proinflammatory capacity and increasing the diversity of the intestinal microbiota, thereby combating pathogenic microorganisms. Notably, there was a significant increase (p<0.05) in the abundance of Proteobacteria, Firmicutes, Tenericutes, and Cyanobacteria at the phylum level, as well as Vibrio, Rhodobacter, and Shewanella at the genus level, respectively. These findings indicate that dietary FBAs and 170HDa have positive effects on growth performance and intestinal health by modulating lipid metabolic profiles, immune responses, the integrity of intestinal wall, and the diversity of intestinal microbes in white shrimp. This study suggests that FBAs and 170HDa could serve as effective dietary supplements to enhance shrimp production and health management in aquaculture, providing a promising strategy for sustainable aquaculture practices.